Prediction of NEPSE Index Movement Using Technical Analysis - Joshi, Dushyant Lal (Nepal Journal of Multidisciplinary Research, 2023)
Due to the nature of the stock and index, predicting index or price movements is a challenging task. The nature of index volatility makes it impossible for investors to profit from stocks. To address this problem, investors need to make accurate predictions about future index or stock price changes. In this study, data has collected for 6 months (December 2022 to May 2023) and technical trading tools such as candlesticks and Google Form Questionnaire Surveys were used to determine the movement of the NEPSE index. A questionnaire survey is completed with 62 answers. Given the Nepalese context and due to the global economic crisis and uncertain political environment, as a result, in a bearish market, the candlestick stick pattern produces mixed results while the trader can benefit from it in the very short term, but sometimes does not provide the right and appropriate movement.